Impact of experimental pressure and temperature on semiclathrate hydrate formation for pre-combustion capture of CO2 using tetra-n-butyl ammonium nitrate - Babu, Ponnivalavan; Datta, Stuti; Kumar, Rajnish; Linga, Praveen (Energy, 2014)
TBANO(3) (tetra-n-butyl ammonium nitrate) is a promising liquid phase promoter for capturing CO2 via HBGS (hydrate based gas separation) technology. In this study, the impact of experimental pressure and temperature on formation of mixed CO2-H-2-TBANO(3) semiclathrate hydrate for the optimum 1.0 mol% TBANO(3) reported by Babu et al. [1] was investigated. Experimental pressures of 3.0, 4.5 and 6.0 MPa and temperatures of 274.2, 276.2 and 278.2 K were employed. Irrespective of the experimental pressure, shorter induction time was observed for experiments conducted at 274.2 K when compared to the experiments at other temperatures. At a given pressure, the total gas uptake increased with increase in experimental temperature. Similarly at a given temperature, the total gas uptake increases with an increase in pressure. Higher rate of hydrate formation was observed at experimental pressure of 6.0 MPa than at 3.0 and 4.5 MPa irrespective of the experimental temperature. The CO2 composition in hydrate was between 87.5 and 93.2 mol%. Finally, the gas consumption for 1.0 mol% TBANO(3) as promoter was much higher than other promoters of quaternary salts like tetra-n-butyl ammonium bromide and tetra-n-butyl ammonium fluoride at comparable concentration and driving force. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide capture; Clathrate process; Gas hydrates; Semi-clathrates